Biomechanical analysis of male long jump techniques of selected Oromia regional state clubs - Wondirad, Samson; Eba, Amanu; Khan, Asim (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2021)
Ethiopia is the potential area in order to produce world class jumpers. However, intensive work has been never done on the area of biomechanical analysis work. Thus, this research project is designed to assess the Biomechanics analysis long jumpers on Oromia region athletic clubs. The study was used explanatory research design and gathered data once from the subjects. Availability sampling technique was used in order to select jumpers (n = 20) and document analysis. For the purpose of data analysis, motion analysis software Kinovea was used to analyze video records. Then, quantitative data obtained from the motion analysis software were entered to further analysis into SPSS.Version 23. Pearson product moment correlation coefficient was used to found-out the relationship between long jumpers’ seasonal best performance and long jump phases joint angles. Multiple regressions coefficient was used to analyze the effect of release parameters angles at release during take-off on jumping distance. The result of this study shows long jump Take off Preparation Knee have significant relationship with long jumpers jumping performance (r = -0.67, p<0.05) and long jump Take off knee have significant relationship with seasonal jumping performance of long jumpers (r = -0.53, P< 0.05. Knee angle during take-off preparation phase and take off phase explained by 67.6% of variance (R2=.676, F(18, 2.72) =, 15.1, p < 0.05). Effect size of long jump take off preparation knee angle was significant (R2=.676, F (18, 2.72) =, 15.1, Beta value (B) = -0.016, p < 0.05) and long jump take off knee angle (R2=.676, F (18, 2.72) =, 15.1, Beta value (B) = -0.014, p < 0.05). In conclusion, both phases (take off preparation and take off), knee have low effect size on long jumpers’ seasonal performances.